Analisis Prosedur Pemuatan Jumbo Bag di KM. Royal Glory - Muhammad Bayuseto; Amthori Anwar; Fitri Suprapti; Erwin Sutantyo (Jurnal Maritim Polimarin, 2025)
The optimization of cargo loading processes plays a crucial role in maritime logistics operations. This study is focused on examining jumbo bag loading procedures aboard MV Royal Glory, identifying various influencing factors, and establishing management methods for damaged jumbo bags. Using a qualitative-descriptive approach, data was collected through field observations, in-depth interviews, and documentation during sea practice. Research findings show that while loading procedures are systematically structured, their effectiveness remains limited as they rely on manual calculations and crew expertise without technological support. Three primary constraints identified include human resources, equipment and facilities, and cargo materials. Although measures for handling damaged jumbo bags have been implemented, preventive actions have not yet been adopted. This situation leads to reduced operational time efficiency and heightened occupational safety risks.